Avaliação das concentrações de material particulado, NO2 e SO2 resultantes dos serviços de pavimentação asfáltica em um ambiente urbano - Barbosa, Lucas Melo (2019)
Road infrastructure works are needed to transport people and goods, but there is a increasing need to develop sustainable building methodologies to collaborate with environmental preservation and human health. In this sense, paving services can impact negatively to air quality standards, especially through the use of asphalt materials, which can generate atmospheric emissions containing various pollutants. In this regard, the present study evaluated the emissions of Particulate Matter (PM), nitrogen dioxide (NO2) and sulfur dioxide (SO2) in the three stages involving the execution of an asphalt layer: mixing, transportation and placement of asphalt mixtures, located in the Metropolitan Region of Fortaleza, Ceará, in an urban environment. The objective of this work was to verify which concentrations are the result of these processes, if these activities may be relevant to atmospheric air degradation, regarding the pollutants evaluated, and which factors play an important role in the various dispersion phenomena of these pollutants, contributing to more severe concentrations or not. For this purpose, active sampling methods were used for PM collection in asphalt plants and passive sampling methods for NO2 and SO2 sampling performed at all stages to evaluate the contribution of using asphalt mixtures throughout this constructive process. The results showed that only NO2 concentrations, in some situations, were below the limits established by national and international legislations regarding air quality standards, while all values obtained from PM and SO2 exceeded the adopted values. It was verified that the meteorological variables may have been of great relevance to the concentrations obtained in this study, besides the amount of asphalt mixture produced in the case of mixing, and the conditions of asphalt mixtures placement, where the highest relation between height of buildings around the site and track width, for example, may have made it difficult to disperse the pollutants collected.